Carnival quest - Mull, Brandon, 1974- (Mull, Brandon, 1974- Candy shop war, 2023)
The Blue Falcons--the secret club of kids who use magical candy to fight and save the world from a family of evil magicians--have defeated two of the family's villainous magician siblings. Now, there is just the third sibling left, Camilla, whose Dreams and Screams International Carnival has arrived in the Blue Falcons' hometown of Colson, California. The only thing is, to enter the Carnival they must leave their arsenal of magic candy behind.